PEMBELIAN MINUMAN KOPI ONLINE DI MASA PANDEMI COVID 19 - Yosini Deliana; Gema Wibawa Mukti; Lucyana Trimo (Universitas Galuh, 2022)
Recently people used to get leisure time by dringking coffeee in coffee shop. The habit become their lifestyle now, especially from youth generation in big city such as Jakarta and Bandung. Along with the times, coffee shop also change its function, not only for leisure but also for social interaction, a gathering place for young people, the confortable place for meeting, the best place for breakfast (Solikatun et al. 2015). The habit of drinking coffeee has continued during Covid-19, so the consumer change behaviour from off line to on line. The coffee shop categorized as good, medium and poor coffee shops based on the variety of coffeee beverage, the number of visitors, taste, price of coffeee beverage and the brand of coffee shop. The objective of this research were to analyze (1) the selection of coffee shop based on consumer criteria, (2) consumers’s reason for online shopping, (3) the relationsip between experiential marketing and consumer loyalty. This research was conducted online in Bandung Januari 2021. The results of this research are considered by coffee shop in running their business online.